THE INFLUENCE OF LOCATION ACCESSIBILITY ON PUBLIC SATISFACTION WITH SERVICE QUALITY SEI VILLAGE EQUIPMENTS LIKE DROWING AS INTERVENING VARIABLES (Case Study in Sei Suka Deras Village Community, Batu Bara District) - Andri Ekawati, Yuni; O Tambunan, Jubelando; Nur Asima Sidabutar, Melisa; Jusnita Samosir, Herna; Yunardi, Yunardi (Universitas Efarina, 2022)
This study aims to find out how the influence of location accessibility on community satisfaction with the quality of service of Sei Suka Deras Village Officials as an Intervening Variable. The research method used is the method of qualitative data and quantitative data. While the data used is primary data. The method of data analysis in this study used simple linear regression analysis to obtain a comprehensive picture of the influence between the variables of Community Satisfaction Location Accessibility by using the SPSS 25 for Windows program. To find out whether there is a significant effect of the independent variable on the dependent variable, a simple linear regression model is used. The results of hypothesis testing using simple regression analysis and t-test show that